Preclinical immunogenicity and protective efficacy of a SARS-CoV-2 RBD-based vaccine produced with the thermophilic filamentous fungal expression system Thermothelomyces heterothallica C1 - Gonzalez-Hernandez, Mariana; Kaiser, Franziska Karola; Steffen, Imke; Ciurkiewicz, Malgorzata; van Amerongen, Geert; Tchelet, Ronen; Emalfarb, Mark; Saloheimo, Markku; Wiebe, Marilyn G.; Vitikainen, Marika; Albulescu, Irina C.; Bosch, Berend-Jan; et al. (Frontiers in Immunology, 2023)
The emergency use of vaccines has been the most efficient way to control the ongoing COVID-19 pandemic. However, the emergence of SARS-CoV-2 variants of concern has reduced the efficacy of currently used vaccines. The receptor-binding domain (RBD) of the SARS-CoV-2 spike (S) protein is the main target for virus neutralizing (VN) antibodies. Here, we evaluated the immunogenicity and efficacy of a SARS-CoV-2 RBD vaccine candidate produced in the Thermothelomyces heterothallica (formerly Myceliophthora thermophila), C1 protein expression system, in a Syrian golden hamster (Mesocricetus auratus) infection model. One dose of 10 µg RBD vaccine based on SARS-CoV-2 Wuhan strain, coupled to a nanoparticle in combination with aluminum hydroxide as adjuvant, efficiently induced VN antibodies and reduced viral load and lung damage upon SARS-CoV-2 challenge infection. The VN antibodies, neutralized SARS-CoV-2 variants of concern D614G, Alpha, Beta and Gamma. Our results support the use of the Thermothelomyces heterothallica, C1 protein expression system to produce recombinant vaccines against SARS-CoV-2 and other virus infections, in order to help overcome limitations associated with the use of mammalian expression systems.